Спектральний аналіз деяких графів з нескінченними променями - Лебiдь, В.О.; Нижник, Л.П. (Український математичний журнал, 2014)
Проведен подробный спектральный анализ счетных графов, которые созданы присоединением к вершинам конечного графа полуограниченных бесконечных цепочек. Охарактеризован спектр матрицы смежности таких графов, построена спектральная мера, приведены в явном виде собственные векторы и спектральное разложение по собственным векторам. We perform a detailed spectral analysis of countable graphs formed by joining semibounded infinite chains to vertices of a finite graph. The spectrum of a self-adjoint operator generated by the adjacency matrix of the graph is characterized, the spectral measure is constructed, the eigenvectors are presented in the explicit form, and the spectral expansion in eigenvectors is obtained.